Asymptotic Analysis of Optimal Uniform Two-Dimensional - Peric, Z. H.; Nikolic, Z.B.; Drajic, D.B (Elektronika ir Elektrotechnika, 2004)
The simple and complete asymptotical analysis is given for a uniform two-dimensional quantizer for Laplace source with the respect to the mean-square error. The significant gain over the optimum uniform scalar quantization is obtained (about 6.8 dB for the rate of 8 bits per sample). The obtained gain using rectangular cells can even be compared to the boundary gain in highdimensional space. Ill. 1, bibl. 6 (in English; summaries in Lithuanian, Russian, English).